Stress paths of confined concrete in axially loaded circular concrete-filled steel tube stub columns. (15th October 2018) - Lin, Siqi; Zhao, Yan-Gang; He, Liusheng
Highlights: Stress paths of confined concrete in the whole-section-loaded CFT columns and corresponding stress path effects are investigated. The influences of column parameters upon the stress paths of confined concrete in whole-section-loaded CFT columns are different from those in concrete-loaded CFT columns. The confinement effects of the concrete in whole-section loaded CFT columns are generally worse than those in concrete-loaded CFT columns. For the confinement coefficient less than about 0.2, the confinement effects of the concrete in CFT columns under the two loading conditions are nearly the same. A compressive strength model incorporating the stress path effect was developed for the confined concrete in CFT columns under two loading conditions. Abstract: Previous study has suggested that the stress paths of confined concrete in concrete-filled steel tube (CFT) stub columns influence the compressive strengths of the concrete, which, however, is based on the test of concrete-loaded CFT columns. In this paper, to fully understand the compressive strength of confined concrete in CFT column, the stress paths of confined concrete in the whole-section-loaded CFT columns are investigated. A detailed parametric study is conducted on the stress paths and their corresponding effects on compressive strength. Test results suggest that the lateral stress of the concrete in a whole-section-loaded CFT column generally occurred in a later stage and less significant than that in a concrete-loaded CFT column. The compressive strength of confined concrete in the whole-section-loaded CFT column with a small confinement coefficient is path-dependent, and the confinement effect of the concrete is generally weaker than that in concrete-loaded CFT column. With the increase of the confinement coefficient, the compressive strengths of confined concrete in whole-section-loaded CFT columns become path-independent. Based on the test results, a compressive strength model incorporating the stress path effect is developed for confined concrete in both whole-section-loaded and the concrete-loaded CFT columns. Good agreement between the experimental results and the ones predicted by the model is found, indicating a high performance of the proposed model.